2020
DOI: 10.7759/cureus.6711
|View full text |Cite
|
Sign up to set email alerts
|

Making a Diagnosis of Common Variable Immunodeficiency: A Review

Abstract: Common variable immunodeficiency (CVID) is a condition that inhibits the function of the immune system, making those with the condition more susceptible to infection from external pathogens, including bacteria and, less often, viruses. The immune disorder is marked by low immunoglobulin levels of immunoglobulin G (IgG) and IgA as well as IgM in some patients. These immune abnormalities typically result in recurrent sinopulmonary infections and can result in serious complications such as pneumonia and chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Another interesting aspect in this case is the development of PJP in a patient with CVID. CVID is a heterogeneous group of immune deficiencies characterized by low immunoglobulin levels thought to be secondary to failure in B cell differentiation and in activation of antibody secretion [ 8 ]. Common respiratory complications in CVID patients include pneumonia, sinusitis and bronchiectasis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting aspect in this case is the development of PJP in a patient with CVID. CVID is a heterogeneous group of immune deficiencies characterized by low immunoglobulin levels thought to be secondary to failure in B cell differentiation and in activation of antibody secretion [ 8 ]. Common respiratory complications in CVID patients include pneumonia, sinusitis and bronchiectasis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…T cell lymphopenia is one of the most important risk factors for Pneumocysti s infection because CD4 + T cells play an essential role in the clearance of the organisms after inhalation from the environment [ 3 ]. CVID is not classically associated with T cell immunodeficiency, but there have been studies showing T cell proliferation and subsequent cytokine release can be affected in CVID patients [ 8 ], which might put our patient at increased risk for PJP.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, people suffering from CVID will differ in their ability to elicit effective antibody responses due to the lowered levels of immunoglobulin. We can distinguish three types of disorders here; the first one concerns the three main types of immunoglobulins (IgG, IgA, and IgM), the second one concerns disorders within IgG and IgA, and the third group concerns those in which only IgG is lowered [213,214]. A diagnosis of CVID is usually confirmed by abnormal blood tests and medical history.…”
Section: The Role Of the Foxp3 Protein In The Development Of Cvidmentioning
confidence: 99%
“…Common variable immunodeficiency (CVID) is one of the most prevalent Primary Antibody Disorders characterized by marked hypogammaglobulinemia 1 . The real incidence of CVID is not simple to ascertain, but the estimated prevalence of CVID in Caucasians ranges between 1:10.000 and 1:50.000 and the prevalence rate may continue to increase 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Delays in diagnosis and treatment worsen the prognosis of CVID patients lead to permanent organ structural damage [1][2][3] . Although few studies reported miRNAs regulation in response to Ig replacement therapy in immunodeficiencies, to our knowledge, there are no studies about miRNAs dosage and changes in CVID patients [10][11][12] .…”
mentioning
confidence: 99%